PENGARUH INISIASI MENYUSU DINI (IMD) TERHADAP JUMLAH DARAH KALA IV PERSALINAN - Irma Nurianti; Tati Murni Karo Karo; Sri Melda Bangun; Sri Yana (JURNAL KEBIDANAN KESTRA (JKK), 2020)
Early Breastfeeding Initiation (EBI) or the onset of early breastfeeding is to give newborns the opportunity to suckle themselves on their mothers in the first hour of birth, Early Breastfeeding Initiation (EBI) is related to the production of the hormone oxytocin, which helps the uterus contract so that it does not can immediately reduce bleeding in the mother. The Early Breastfeeding Initiation (EBI) itself is still low in Indonesia, North Sumatra contributes to the low rate of EBI implementation at 24%, according to the Director General of Family Health of the Ministry of Health Eni Gustina. The biggest cause of maternal mortality in Indonesia during 2010-2013 was bleeding 30.3 %. The purpose of this study was to determine whether there was an effect of early breastfeeding initiation (EBI) on the amount of bleeding period IV in the midwife clinic Suherni Amd. Keb Kec Beringin kab Deli Serdang in 2019. This type of research is pre-experiment with the design of static group comparison, with a population of 28 post partum mothers. Sampling is done by "purposive sampling", the sample size in this study amounted to 20 mothers then divided into 2 groups where 10 mothers as the experimental group and 10 mothers as the control group. Data collection is recorded on the observation sheet, data analysis is done by univariate and bivariate with t-independent test. The results of the analysis showed that there was an effect of Early Breastfeeding Initiation (EBI) on the amount of Bleeding Period IV in the Midwife Clinic Suherni Amd. Keb Kec Beringin Kab Deli Serdang in 2019 with a value of p 0,000. It is expected that the number of mothers who breastfeed in the first minute to one hour of birth can increase, because EBI provides many benefits for babies and mothers. If immediately breastfeeding after giving birth can reduce maternal mortality.